Integration of information systems in the design of an integrated logistics platform (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2021)
Each logistics information system has its own storage. This is due to the fact that the companies that form the supply chain are independent and may have different legal statuses, legal documents, etc. But in order to ensure the smooth and adequate operation of the platform when making decisions, it is necessary that the data and applications of one system be recognizable in another system. Therefore, integration is needed at several levels. The main goal of the study is to showpossible ways of creating integrations starting from the system design stage. Integration theory is a complex task, so it needs to be comprehensively considered. All integration processes are reduced to data integration and software integration. The analysis of integration methods is carried out, as well as factors that negatively affect the integration possibilities are considered. Solutions of integration problems, to ensure the optimization of the design process (reduction of the design time) and design of the system itself (minimization of the content of the system), and during the operation of systems, optimization of its functioning (behavior) of the system. As a result of the study, the need to create data integration and application integration that allows you to structure data is shown. It should be noted that data can be located at all levels of the system architecture. And the system software can be: software modules, applications and systems. The basis of all types of system software, i.e. applications and an integral system are made up of software modules, design and development of software (i.e. based on programming systems) is based on service-oriented technologies, where the basis of systems is software services. The research carried out can be used in the development of information systems.Keywords: information system, platform, integration, services, data.